Robotic Vacuum Cleaner Prototype Integrated with Arduino Uno - Mohd Shaharuddin, Muhammad Faisal; Setafa, Muhamad Saifullah; Sidek, Noor Azizah; Kusairy, Anas (Multidisciplinary Applied Research and Innovation, 2022)
With the vacuum machine available nowadays it is also very unsuitable to take to a residential college because it is very large as equipment to clean the room. This is because the large size will make it difficult for a person to carry a vacuum to enter the room especially students who are staying upstairs. In addition, the vacuum nowadays will also cause anyone who uses it will need a lot of energy. It is because, during the use of the vacuum, we need to bring the machine together because it has a pipe that connects to the garbage collection place inhaled. So high energy consumption is required while using the machine and will tire students to do the work This project aims to test run the hardware (design of the vacuum cleaner) and software (Arduino Uno) to operate in the ideal working environment. The scope of the project should be given as a guide to ensure that the project does not deviate from the goals to be accomplished any time it is implemented. The Use of WiFi and Bluetooth controlled that can be connected within 20 to 30 meters range only. A small prototype is built up to fabricate the design of the robotic vacuum cleaner that is ready for integration with Arduino Uno. The size of the prototype is built with dimensions 30cm x 20cm x 15cm. We take this size because we don’t want a larger size as it will occupy more space.